Application of X-ray micro-CT for micro-structural characterization of APCVD deposited SiC coatings on graphite conduit. (February 2016) - Agrawal, A.K.; Sarkar, P.S.; Singh, B.; Kashyap, Y.S.; Rao, P.T.; Sinha, A.
Abstract: SiC coatings are commonly used as oxidation protective materials in high-temperature applications. The operational performance of the coating depends on its microstructure and uniformity. This study explores the feasibility of applying tabletop X-ray micro-CT for the micro-structural characterization of SiC coating. The coating is deposited over the internal surface of pipe structured graphite fuel tube, which is a prototype of potential components of compact high-temperature reactor (CHTR). The coating is deposited using atmospheric pressure chemical vapor deposition (APCVD) and properties such as morphology, porosity, thickness variation are evaluated. Micro-structural differences in the coating caused by substrate distance from precursor inlet in a CVD reactor are also studied. The study finds micro-CT a potential tool for characterization of SiC coating during its future course of engineering. We show that depletion of reactants at larger distances causes development of larger pores in the coating, which affects its morphology, density and thickness. Highlights: Prepared SiC coating over the internal surface of fuel tube. Micro-structure studied using X-ray micro-CT and quantitative image analysis. Porosity, morphology, coating thickness variation is visualized and measured. Structural differences due to reactant depletion at varied substrate distance are compared.